Known knowns and known unknowns of immigrant self-employment: Selected issues - Joanna Nestorowicz (University of Warsaw, Centre of Migration Research (CMR), 2011)
The paper presents a review of selected definitional issues, theoretical concepts and most recent empirical evidence related to the phenomenon of immigrant self-employment. Based on the appraisal of gathered material it also points to possible areas of development of future research in the field.
Keywords: B2; F22; J6; 330; migration; self-employment; ethnic entrepreneurship; middleman minority; ethnic enclave; literature review; state of the art; Migranten; Selbstständige; Unternehmer; Ethnische Gruppe; Diskriminierung; Theorie